Privasi Rumah Kediaman dalam Islam sebagai Panduan kepada Pembangunan Perumahan (Jurnal Pembangunan Sosial, 2015)
The dwelling is part of the basic needs in human life. In Islam, the designation of a place as a dwelling has its own importance. The dwelling is not only seen as a sanctuary for oneself and his property it is also signifcant in privacy space. This paper aims to discuss privacy related to dwelling house in Islamic jurisprudence. The discussion will focus on the importance of the privacy rules for a dwelling to be used as a guide to the parties involved to housing development. In general, Islam provides a balance between the social life and the need to be alone at a time. The principles of privacy for a dwelling not only show security of shariah objectives but guide for the construction industry with divine guidance in sustainable human development.